PEMAHAMAN PLURALISME DALAM PERSPEKTIF AJARAN ISLAM DALAM KONTEKS PENDIDIKAN MULTIKULTURAL - Fitri Ayu Ilahana Ilahana; Syakira Salmanida; Ahmad Manshur (STKIP Subang, 2026)
The multifaceted nature of tribes, cultures, languages, and religions present in Indonesia engenders a pluralistic social reality among its populace. This scenario necessitates a to facilitate the harmonious navigation of diversity. The objective of this research is to elucidate the concept of pluralism within the Islamic teaching framework and to evaluate its pertinence within the realm of multicultural education. The research employs a qualitative methodology, characterized by a library research approach. Data were acquired through a documentation methodology that encompassed literature reviews from Google Scholar academic databases and nationally indexed SINTA journals, utilizing sampling techniques designed to identify pertinent sources published in the preceding decade. The results indicate that the notion of pluralism in Islamic teachings is robustly endorsed by theological principles derived from the Qur'an and Hadith, encompassing the teachings of ta'aruf, la ikraha fi al-din, and the universal concept of ummat. The tenets of Islamic pluralism, including tasamuh, tawazun, i'tide, and ukhuwah, exhibit substantial congruence with the objectives of multicultural education. The operationalization of these principles within the educational sphere can be realized through an integrative curricular approach, the establishment of an inclusive educational environment, and the proactive engagement of educators. In conclusion, when Islamic teachings are interpreted in a comprehensive and contextual manner, they furnish a robust foundation for fostering a peaceful and harmonious communal existence, as well as providing a strategic basis for enhancing multicultural education in Indonesia.